The impact of the M-learning methodology on university students - Oscar Romero Ramos; Emilio Fernández Rodríguez; Iván López Fernández; Rafael Merino Marbán; Javier Benítez Porres (OmniaScience, 2022)
Our goal in this paper is to analyse the impact of the implementation of M-Learning methodology on the motivation and assimilation of academic contents. A total of 283 university students participated in our study. They were assessed on two different occasions. For the assessment, a 10-question multiple-answer test set up in the Socrative mobile applications was used. To take into consideration the students' opinion on the experiment a satisfaction survey was used. The results from the global satisfaction survey show that the M-Learning methodology is perceived as a motivating tool (74.6%) which generates a more pleasant environment in the classroom (71%), increases student satisfaction attending classes (80.5%) and helps students acquire learning contents better (72.5%). The repetition and frequency of use of the application increased the final score in all groups (initial-final assessment: 5.9 vs 7.4 points). Data obtained suggest that the M-Learning methodology as a facilitator of content assimilation is useful in the academic environment and is a useful tool for improving the teaching-learning process too.